Religion to Promote the Authentic Values of a Nation - Cacciavillan, Agostino (Journal of Dharma, 1983)
Because of the very nature of my mission of representing the Holy Father, the Pope, to be his Pronuncio to India, I deem it a rare privilege to be open to friendship with each one of you; and friendship obviously has a religious connotation. Let me be a little informal in saying that I really feel very happy in the presence of all of you. My message is a religious one, and to begin with, it is a message of friendship which 1 may extend to all of you who are in the fellowship of religious pursuits.